Visual self-motion information contributes to passable width perception during a bike riding situation - Kuroda, Naoki; Ikeda, Kazuhiro; Teramoto, Wataru (Frontiers in Neuroscience, 2022)
Previous studies have shown that space perception around the body is altered by self-motion, and that several self-motion cues from different modalities, including vision, proprioception, the vestibular system, and the motor system (motor commands) contribute to it. However, studies on how online self-motion information affects the perception of a passable width of a narrow aperture is largely overlooked by existing literature. Therefore, this study investigated this issue during virtual bike riding. Participants observed a narrow doorway aperture with varied widths in a virtual environment through a head-mounted display while riding a stationary bike. Visual self-motion information was presented by optical flow, while motor commands and proprioceptive feedback (non-visual information) was provided by having participants pedal the bike. The participants were then required to judge whether the presented aperture was passable. Experiment 1, where both visual and non-visual cues were provided, confirmed that the perceived passable width significantly increased with increasing self-motion speed, as previously shown during walking. Experiment 2, where self-motion cues were manipulated, showed that expansion of the perceived passable width was mainly induced by visual self-motion information. These results suggest that online self-motion information can affect passable width perception during bike riding and that visual self-motion information plays a significant role in this perception.